Stages of global sourcing strategy evolution: an exploratory study - Bozarth, Cecil; Handfield, Robert; Das, Ajay (Journal of Operations Management, 1998)
AbstractThis paper analyzes the interrelationships between international sourcing decisions, sourcing strategies, and supplier performance. We first discuss the effect of global competition on the need for firms to seek international suppliers, and present a number of taxonomies that describe the evolution of global supply base development. The deployment of different commodity strategies (e.g., information sharing, single vs. multiple sourcing, contracts, and partnering) in conjunction with international sourcing is also reviewed. In the second half of the paper, we examine a set of international sourcing practices from a sample of 55 US manufacturing firms. Results suggest that US purchasing professionals are not spending as much time managing the ongoing buyer–supplier relationship as they are making the initial purchasing decision. This gap between ‘prescription’ and ‘practice’ represents both a competitive opportunity and threat for manufacturers.